ISOLASI FRAKSI SITOTOKSIK IN VITRO TERHADAP SEL KANKER LEHER RAHIM (HeLa) DARI EKSTRAK KLOROFORM BUAH MERAH (Pandanus conoideus Lamk.) VARIETAS MALER - , WAHYUDI, Prof. Sukarti Moeljopawiro, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Recently buah merah has been extensively used to treat cancer. The scientific studies of anticancer activity of buah merah on the growth of cancer are relatively very few. It was found that the best extract that had the highest toxicity on breast cancer and cervic cancer cells was chloroform extract of Maler. But the compound of those extract has not be identified and isolated. Therefore the objective of these studies were to identify and isolate the in-vitro cytotoxic fraction on cervic cancer cells from chloroform extract of buah merah (Pandanus conoideus Lamk.) Maler variety. Buah merah local variety Maler and cancer cell line HeLa were used in this study. Buah merah was extracted using chloroform. The extract was fractionated using vacuum coloumn chromatography followed by TLC. Cytotoxicity was performed using MTT assay. The IC50 was determined using linear regression analysisis.The toxic compound of the most toxic fraction was separated using preparative TLC. The products of preparative TLC were the lower position, middle position and upper position were tested using a MTT assay. Profile of the highest cytotoxic fraction was monitored by TLC using n-hexan (4 ml) : aceton (4 ml) : glacial acetic acid (6 drops) as a solvent system. This study showed that the low position of preparative TLC profile had the lowest IC50 (109.99 Âµg/mL). Chloroform extract of buah merah Maler variety 75.20 gram could produce 0.166 gram cytotoxic fraction. Chromatogram TLC of those cytotoxic fraction showed that the profil was similar to toxic compound on breast cancer T47D. It could be concluded that the cytotoxic fraction in chloroform extract of buah merah Maler variety could be separated using preparative TLC. The ratio of extract and cytotoxic fraction on cervic cancer was 453 : 1.